Wallerian degeneration as a therapeutic target in traumatic brain injury - Koliatsos, VE (Curr Opin Neurol, 2019)
PURPOSE OF REVIEW: Diffuse or traumatic axonal injury is one of the principal pathologies encountered in traumatic brain injury (TBI) and the resulting axonal loss, disconnection, and brain atrophy contribute significantly to clinical morbidity and disability. The seminal discovery of the slow Wallerian degeneration (WD) mice (Wld(s)) in which transected axons do not degenerate but survive and function independently for weeks has transformed concepts on axonal biology and raised hopes that axonopathies may be amenable to specific therapeutic interventions. Here we review mechanisms of axonal degeneration and also describe how these mechanisms may inform biological therapies of traumatic axonopathy in the context of TBI. RECENT FINDINGS: In the last decade, SARM1 and the DLK/LZK MAPK cascade have been established as the key drivers of WD, a complex program of axonal self-destruction which is activated by a wide range of injurious insults, including insults that otherwise leave axons structurally robust and potentially salvageable. Detailed studies on animal models and postmortem human brains indicate that this type of partial disruption is the main initial pathology in traumatic axonopathy. At the same time, the molecular dissection of WD has revealed that the decision that commits axons to degeneration is temporally separated from the time of injury, a window that allows potentially effective pharmacological interventions.